Kepemimpinan Gender dalam Pengambilan Keputusan Pemerintahan di Kota Baubau - Amalia, Adefitri; Gazalin, Junaid; Suharni, Wa Ode; Ratna, Ratna; Arham, La Ode Muhammad (CV. ULIL ALBAB CORP, 2025)
This article examined gender in leadership which is still be a topic of discussion that attracts a lot of attention. Which aims to discuss women's leadership style, leadership effectiveness, relations of gender in leadership, the glass ceiling and labyrinth which is barriers in leadership for women, and the motive of removing gender barriers in leadership. This article used the literature review method, with references from several previous studies that raised similar topics. Based on the sources that have been collected, the results of this literature review revealed that gender is still a significant factor in leadership practice, especially in high levels of leadership dominated by men. In addition, research shows that there are differences in leadership styles between men and women. Men tend to attach importance to aspects of duty and authority, while women tend to use a participatory and relationship-building approach. Both of these leadership styles have their own advantages and disadvantages, and it is important to consider the context of the organization and the associated tasks.